Considering emigration: German university graduates are moving abroad - But only temporarily - Elisabeth Liebau; Jürgen Schupp (Weekly Report, 2011)
Much of the current German debate about the integration of immigrants overlooks the fact that Germany is not solely a country of immigration, but also - and to a substantial degree - a country of emigration. One of the largest groups of emigrants is made up of Germans themselves. The percentage of German natives in the total population of emigrants has risen substantially over the last few years. In 2009, of the almost 750,000 individuals who emigrated from Germany, 155,000 were German citizens. Data from the Socio-Economic Panel (SOEP) show that in 2009, one in every eight German citizens seriously considered moving abroad. Of these, one in three considered leaving Germany permanently and one in eleven considered leaving within the next twelve months. Of the factors that tend to favor emigration, previous experiences and friends abroad play a crucial role. University graduates are more inclined to move abroad temporarily. Concerns that Germany is suffering a brain drain, losing its best and brightest to other countries, are therefore unjustified at the present time.
Keywords: C81; D01; O15; 330; SOEP; migration; mobility